Organizational Change? Organizational Development? Organizational Transformation?: Why Do We Care What We Call It? - Jacqlyn S. Triscari (Adult Education Research Conference, 2008)
This paper represents a literature review on the topic of organizational change. It argues that how we label a specific type of organizational change has an impact on how we both view the change and the potential outcome. The focus here is on transformational change—a change that occurs at the center core of the organization and results in substantial change to the center core of the organization, impacting the currently held beliefs and assumptions.
Keywords: organization; transformation; change; organizational development